Hp → Hp boundedness implies Hp → Lp boundedness - Yongsheng Han; Ji Li; Guozhen Lu; Peiyong Wang (Forum Mathematicum, 2011)
Permanently implanted iodine-125 (125I) brachytherapy sources are a radiological technique used to treat localized cancers. The TG-43U1 group of the AAPM emphasizes the importance of calculating the dose distribution around brachytherapy seeds before their clinical use or approval for therapeutic purposes. In this work, we examined the dosimetric properties of the BEBIG iodine-125 IsoSeed I25.S06 source for LDR brachytherapy, based on the TG-43U1 guidelines. Dose calculations were carried out using Monte Carlo simulations with Python. The results are interesting. The analysis aimed to determine several dosimetric parameters, such as the radial dose function gL(r), the anisotropy function F(r,θ), and the dose rate constant Λ were determined. Furthermore, Comparison with previous studies reveals a good level of agreement. The Python code appears to provide results in good agreement with expected values for the dosimetry parameters.